THE INFLUENCE OF CORPORATE FINANCIAL PERFORMANCE ON SHARE RETURN - Ghulam Nurul Huda; Bonar M. Sinaga; Trias Andati (Indonesian Journal of Business and Entrepreneurship (IJBE), 2015)
This study was conducted to examine the effect of financial performances of Economic Value Added (EVA), Market Value Added (MVA) as well as financial ratios (Fixed Asset Turnover, Return on Investment, Debt to Equity Ratio, Price to Book Value, Total Asset Turnover) on Stock Return. This study used the data of six representative palm oil companies which were listed in Indonesia Stock Exchange. The analysis models that were used included three multiple regression equations for EVA, MVA and Stock Return. The results indicate that DER significantly influences EVA and PBV, and TATO significantly influences MVA. Return Shares are significantly only affected by EVA. The company's fundamentals, especially EVA, PBV, TATO and DER were used by investors to predict the Stock Return in Indonesia Stock Exchange in 2009–2014 period. This study confirmed the previous studies that these variables are involved on regression model to predict the Stock Return. The results of the analysis of the company's financial performance with EVA and MVA and financial fundamental variables provide a better alternative picture on the achievement of the company so that the benefits in investing in the palm oil business in Indonesia can be maximally managed.Keywords: Indonesia Stock Exchange, investor, market, multiple regression, stockAbstrakPenelitian ini dilakukan untuk menguji pengaruh kinerja keuangan Economic Value Added (EVA) dan Market Value Added (MVA), serta rasio keuangan (Fixed Asset Turnover, Return on Investment, Debt to Equity Ratio, Price to Book Value, Total Aset Turnover) terhadap Return Saham. Penelitian ini menggunakan enam sampel perusahaan produsen minyak sawit yang terdaftar di Bursa Efek Indonesia. Model analisis yang digunakan adalah tiga persamaan regresi berganda untuk EVA, MVA dan Return Saham. Hasil penelitian menunjukkan bahwa DER berpengaruh signifikan terhadap EVA. PBV dan TATO berpengaruh signifikan terhadap MVA. Return Saham hanya dipengaruhi secara signifikan oleh EVA. Faktor fundamental perusahaan terutama EVA, PBV, TATO dan DER digunakan oleh investor untuk memprediksi Return Saham di Bursa Efek Indonesia pada periode 2009–2014. Penelitian ini mempertegas hasil penelitian sebelumnya yang menyebutkan variabel EVA, PBV, TATO dan DER ke dalam model regresi untuk memprediksi Return Saham. Hasil analisis kinerja keuangan perusahaan dengan EVA, MVA, dan Variabel fundamental keuangan memberikan alternatif gambaran yang lebih baik atas pencapaian yang dilakukan perusahaan sehingga keuntungan yang diperoleh didalam melakukan investasi pada bisnis kelapa sawit di Indonesia dapat dikelola dengan maksimal. Kata kunci: bursa efek Indonesia, investor, pasar, regresi berganda, saham